2009
DOI: 10.1124/dmd.109.029413
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel System for Estimating Human Intestinal Absorption Using Caco-2 Cells in the Absence of Esterase Activity

Abstract: ABSTRACT:Both mRNA and protein levels of the carboxylesterase (CES) isozymes, hCE1 and hCE2, in Caco-2 cells increase in a timedependent manner, but hCE1 levels are always higher than those of hCE2. In human small intestine, however, the picture is reversed, with hCE2 being the predominant isozyme. Drugs hydrolyzed by hCE1 but not by hCE2 can be hydrolyzed in Caco-2 cells, but they are barely hydrolyzed in human small intestine. The results in Caco-2 cells can be misleading as a predictor of what will happen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…Caco-2 cells express CES; however, the expression profiles of CES isoforms differ from those in human small intestine and colon tissue (Ohura et al, 2010). The involvement of CES1 and CES2 on the formation from dabigatran etexilate to the mono-prodrugs BIBR 1087, BIBR 951, as well as dabigatran was investigated under several experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caco-2 cells express CES; however, the expression profiles of CES isoforms differ from those in human small intestine and colon tissue (Ohura et al, 2010). The involvement of CES1 and CES2 on the formation from dabigatran etexilate to the mono-prodrugs BIBR 1087, BIBR 951, as well as dabigatran was investigated under several experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of CES1-catalyzed BIBR 1087 formation in Caco-2 cells was assessed by conducting transcellular transport experiments with nonlabeled dabigatran etexilate, followed by LC-MS/MS quantification of both dabigatran etexilate and BIBR 1087 in the absence and presence of the CES inhibitor BNPP (Fig. 4) (Ohura et al, 2010). BNPP at a concentration of up to 200 mM did not affect the tightness of the monolayer and P-gp activity, as confirmed by comparing Papp of mannitol, propranolol, and digoxin in the absence and presence of BNPP (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…16 As skin homogenate contains all skin components, that is, pieces of cells, fibers, proteoglycan, and so on, it seems that ethyl-FXD binds not only to protein, but also to proteoglycans and to other components with a lipid phase such as cell membranes. Previously we have reported that ethyl-FXD is accumulated into Caco-2 cells during a transport experiment; 10% of ethyl-FXD was transported into the basolateral compartment, 8% remained on the apical side, and 80% accumulated inside the cell after 2 h. 32 We concluded that ethyl-FXD mainly accumulated in the cellular membrane because of its high lipophilicity and basicity. In the skin, ethyl-FXD is able to accumulate in intact whole cells such as keratinocytes, therefore the bound fraction of ethyl-FXD may be large enough for it to be retained in viable skin.…”
Section: Discussionmentioning
confidence: 99%
“…Masaki et al (2007) also established that nearly complete inhibition of CES is obtained by preperfusion with BNPP (400 M for 40 min). More recently, Ohura et al (2010) reported that BNPP affects neither active transport, e.g., p-glycoprotein, peptide, and organic anion transporters, nor passive diffusion in Caco-2 cell monolayers.…”
Section: Resultsmentioning
confidence: 99%